MANAJEMEN DANA IURAN RUKUN KEMATIAN DI PUNTUN KOTA PALANGKA RAYA - Jirhanuddin, Jirhanuddin; Dakhoir, Ahmad; Sulistyaningsih, Sulistyaningsih (AL-QARDH, 2016)
The existence of rukun kematian (RKM) nowadays is extremely helpful for the society. Therefore, it needs a good management in order to make RKM running well and functioning as the purpose when it was established. However, the result of observation toward RKM Puntun, Palangka Raya showed several inexpediencies about the application of management elements and the distribution of compensation that given by RKM. Then this research discussed about funding management and compensation practices by RKM to its member. There were two problems of the study: (1) How is the funding management in RKM in Puntun, Palangka Raya, (2) Is the distribution of compensation appropriate with ta